COMPARATIVE STUDY ON RASHTRIYA SWASTHYA BHIMA YOJANA AND AYUSHMAN BHARATH PRADHAN MANTRI JAN AROGYA YOJANA IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
As healthy populations are more productive, save more, and live longer, good health is essential to human pleasure and well-being, which makes a considerable contribution to prosperity, wealth, and even economic growth. Health insurance is not a luxury, it is a need. In the event of a medical emergency, having health insurance is useful. India's economy is increasing in the area of health insurance. The health care system in India combines governmental and private providers. India spends less on public health than comparable middle-income nations do. The availability of public health services varies significantly amongst federation states. National health insurance programmes are essentially health initiatives started by the government to provide access to healthcare for the underprivileged. The goal of the current study is to contrast RSBY and AB-PMJAY in India